Great tits (Parus major) flexibly learn that herbivore-induced plant volatiles indicate prey location : an experimental evidence with two tree species - Sam, Katerina (2021)
When searching for food, great tits (Parus major) can use herbivore-induced plant volatiles (HIPVs) as an indicator of arthropod presence. Their ability to detect HIPVs was shown to be learned, and not innate, yet the flexibility and generalization of learning remain unclear. We studied if, and if so how, naïve and trained great tits (Parus major) discriminate between herbivore-induced and noninduced saplings of Scotch elm (Ulmus glabra) and cattley guava (Psidium cattleyanum). We chemically analyzed the used plants and showed that their HIPVs differed significantly and overlapped only in a few compounds. Birds trained to discriminate between herbivore-induced and noninduced saplings preferred the herbivore-induced saplings of the plant species they were trained to. Naïve birds did not show any preferences. Our results indicate that the attraction of great tits to herbivore-induced plants is not innate, rather it is a skill that can be acquired through learning, one tree species at a time. We demonstrate that the ability to learn to associate HIPVs with food reward is flexible, expressed to both tested plant species, even if the plant species has not coevolved with the bird species (i.e., guava). Our results imply that the birds are not capable of generalizing HIPVs among tree species but suggest that they either learn to detect individual compounds or associate whole bouquets with food rewards.